Gene expression analysis of heat-shock proteins and redox regulators reveals combinatorial prognostic markers in carcinomas of the gastrointestinal tract - Sebastian Öther-Gee Pohl; Shazib Pervaiz; Arun Dharmarajan; Mark Agostino (Redox Biology, 2019)
Heat shock proteins (HSPs) are a large family of ubiquitously expressed proteins with diverse functions, including protein assembly and folding/unfolding. These proteins have been associated with the progression of various gastrointestinal tumours. Dysregulation of cellular redox has also been associated with gastrointestinal carcinogenesis, however, a link between HSPs and dysregulation of cellular redox in carcinogenesis remains unclear. In this study, we analysed mRNA co-expression and methylation patterns, as well as performed survival analysis and gene set enrichment analysis, on gastrointestinal cancer data sets (oesophageal, stomach and colorectal carcinomas) to determine whether HSP activity and cellular redox dysregulation are linked. A widespread relationship between HSPs and cellular redox was identified, with specific combinatorial co-expression patterns demonstrated to significantly alter patient survival outcomes. This comprehensive analysis provides the foundation for future studies aimed at deciphering the mechanisms of cooperativity between HSPs and redox regulatory enzymes, which may be a target for future therapeutic intervention for gastrointestinal tumours. Keywords: Heat shock proteins (HSPs), Redox regulators, Gene expression analysis, Gastrointestinal carcinomas